Work, Tourist Encounters and Romantic Involvements in Havana’s Salsa Schools - Ana, Ruxandra (Research Papers, 2019)
The article looks at the practices, expectations and desires developed around Cuban dance, by focusing on the transnational circulation of Cuban dance forms and on dance instruction aimed at foreign audiences. Tourist encounters that take place at informal dance events and parties facilitate the emergence and diversification of narratives around racialized and gendered bodies, while emphasizing the inequalities of international tourism. The article is based on fieldwork conducted in Havana from March to May 2018.